Pengaruh Kemampuan Dinamis dan Digitalisasi Informasi terhadap Kinerja Usaha Kecil dan Menengah (UKM) di Kota Payakumbuh - Feroz, Narajdhiya; Serly, Vanica (Jurnal Eksplorasi Akuntansi, 2025)
This study aims to test the effect of dynamic capabilities and digitalization of information on SME performance. The population used in this study is the performance of SMEs in Payakumbuh City. The sampling technique in this study used the Slovin formula and obtained 81 SME respondents in Payakumbuh City. Data collection was carried out through a survey using an open questionnaire, and analyzed using multiple regression techniques. the results of this study indicate that (1) Dynamic capabilities do not affect SME performance, (2) Information digitalization affects SME performance.